Peningkatan Hasil Belajar Pembelajaran Tematik Terpadu Menggunakan Model Poblem Based Learning di Sekolah Dasar - Noni Rahmadhani; Farida S (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2022)
Basically, this study aims to describe student learning outcomes in integrated thematic learning using the Problem Based Learning (PBL) Model in Class IV SDN 01 Koto Marapak Kota Pariaman. This research is a classroom action research by combining qualitative and quantitative approaches. The subjects in this study were teachers and fourth grade students where the number of male students was 6 and 6 female students. The results showed that in a) planning cycle I obtained an average value of 83.88% with good qualifications (B) increased in cycle II to 91.66% with very good qualifications (SB), b) implementation of learning in the aspect of the teacher cycle I obtained an average score -Average 82.14% with good qualifications (B) increased in cycle II to 92.85% with very good qualifications (SB) and aspects of cycle I students obtained an average score of 76.78% with good qualifications (C) and experienced an increase in cycle II to become 92.85% with very good qualifications (SB), c) student learning outcomes in the first cycle obtained an average value of 65.69% with a moderate success rate (C) then increased in the second cycle to 80.37% with a good success rate (B).